Rates of formal diagnosis of dementia in primary care: The effect of screening - Tilly Eichler; Jochen René Thyrian; Johannes Hertel; Bernhard Michalowsky; Diana Wucherer; Adina Dreier; Ingo Kilimann; Stefan Teipel; Wolfgang Hoffmann (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2015)
Abstract Background Screening could improve recognition of dementia in primary care. We sought to determine the effect of screening for dementia in primary care practices on the formal diagnosis rate; the distribution of differential diagnoses; and the factors associated with receiving a formal diagnosis. Methods The “Dementia: life‐ and person‐centered help in Mecklenburg‐Western Pomerania” is an ongoing general practitioner (GP)‐based, randomized, controlled intervention trial. A total of 4064 community dwelling patients (aged ≥70 years) were screened for dementia in 108 GP practices. Of these patients, 692 (17%) had positive screening results (DemTect score <9). Of these 692 patients, 406 (59%) provided informed consent. The analyses included the data from 243 patients with a complete baseline assessment (preliminary data; January 2014). Results Of 146 patients without a formal diagnosis of dementia, 72 (49%) received a formal diagnosis after a positive screening outcome (69% with “unspecified dementia”). Female sex was significantly associated with receiving a formal diagnosis (multivariate analyses). Conclusion Screening improved the identification of dementia considerably. Because of the risk of receiving a false‐positive diagnosis, additional diagnostic assessment should be mandatory.